On the influences of the continental shelf bathymetry correction in Prydz Bay, East Antarctica - Sun, Chong; Liu, Chengyan; Wang, Zhaomin; Yan, Liangjun; Tao, Yixuan; Qin, Qing; Qian, Jiangchao (Frontiers in Marine Science, 2022)
The bathymetry around Antarctica can govern the shelf sea circulations and play a key role in conditioning water masses. In Prydz Bay, the Prydz Bay Gyre and coastal currents are also determined by the continental shelf topography. However, due to the paucity of beam echo sounding data, the bathymetric datasets in Prydz Bay still have large uncertainties. With the aid of in situ hydrographic observations, this study focuses on the correction of an up-to-date bathymetric dataset and the resultant influences on the shelf circulation and the basal melting of the ice shelves. The corrected bathymetry mainly improves the biased shallow representations in the uncorrected bathymetric data set, with a maximum change of ~500 m deepening in the eastern flank of Prydz Bay. Sensitivity numerical experiments show that the bathymetric corrections in Prydz Bay have a significant impact on the circulation pattern and onshore warm water intrusions. In addition, the corrected bathymetry markedly decreases the heat transport towards the calving front of the Amery Ice Shelf. The onshore heat transport reduces by ~22.18% from ~5.23×1013 J s-1 to ~4.07×1013 J s-1 over the outer shelf. Over the inner shelf, the heat transport towards the Amery Ice Shelf reduces by ~18.15% from ~5.95×1013 J s-1 to ~4.87×1013 J s-1. Consequently, the temporally and spatially averaged basal melting rate of the Amery Ice Shelf reduces by ~13.04% from ~0.69 m yr-1 to ~0.60 m yr-1.